Safety and feasibility evaluation of planning and execution of surgical revascularisation solely based on coronary CTA and FFRCT in patients with complex coronary artery disease: study protocol of the FASTTRACK CABG study. Issue 12 (10th December 2020) - Kawashima, Hideyuki; Pompilio, Giulio; Andreini, Daniele; Bartorelli, Antonio L; Mushtaq, Saima; Ferrari, Enrico; Maisano, Francesco; Buechel, Ronny R; Tanaka, Kaoru; La Meir, Mark; De Mey, Johan; Schneider, Ulrich; et al.
Abstract : Introduction: The previously published SYNTAX III REVOLUTION trial demonstrated that clinical decision-making between coronary artery bypass graft (CABG) and percutaneous coronary intervention based on coronary CT angiography (CCTA) had a very high agreement with the treatment decision derived from invasive coronary angiography (ICA). The study objective of the FASTTRACK CABG is to assess the feasibility of CCTA and fractional flow reserve derived from CTA (FFRCT ) to replace ICA as a surgical guidance method for planning and execution of CABG in patients with three-vessel disease with or without left main disease. Methods and analysis: The FASTTRACK CABG is an investigator-initiated single-arm, multicentre, prospective, proof-of-concept and first-in-man study with feasibility and safety analysis. Surgical revascularisation strategy and treatment planning will be solely based on CCTA and FFRCT without knowledge of the anatomy defined by ICA. Clinical follow-up visit including CCTA will be performed 30 days after CABG in order to assess graft patency and adequacy of the revascularisation with respect to the surgical planning based on non-invasive imaging (CCTA) with functional assessment (FFRCT ) and compared with ICA. Primary feasibility endpoint is CABG planning and execution solely based on CCTA and FFRCT in 114 patients. Primary safety endpoint based on 30 day CCTA is graft assessment and topographical adequacy of the revascularisation procedure. Automatic non-invasive assessment of functional coronary anatomy complexity is also evaluated with FFRCT for functional Synergy Between percutaneous coronary intervention With Taxus and Cardiac Surgery Score assessment on CCTA. CCTA with FFRCT might provide better anatomical and functional analysis of the coronary circulation leading to appropriate anatomical and functional revascularisation, and thereby contributing to a better outcome. Ethics and dissemination: Each patient has to provide written informed consent as approved by the ethical committee of the respective clinical site. Results will be submitted for publication in peer-reviewed journals and will be disseminated at scientific conferences. Trial registration number: NCT04142021 .